Poke weed mitogen requires toll-like receptor ligands for proliferative activity in human and murine B lymphocytes - Bekeredjian-Ding, Isabelle; Förmer, Sandra; Kirschning, Carsten Jürgen; Parčina, Marijo; Heeg, Klaus (PLOS ONE, 2012)
Poke weed mitogen (PWM), a lectin purified from Phytolacca americana is frequently used as a B cell-specific stimulus to trigger proliferation and immunoglobulin secretion. In the present study we investigated the mechanisms underlying the B cell stimulatory capacity of PWM. Strikingly, we observed that highly purified PWM preparations failed to induce B cell proliferation. By contrast, commercially available PWM preparations with B cell activity contained Toll-like receptor (TLR) ligands such as TLR2-active lipoproteins, lipopolysaccharide and DNA of bacterial origin. We show that these microbial substances contribute to the stimulatory activity of PWM. Additional experimental data highlight the capacity of PWM to enable B cell activation by immunostimulatory DNA. Based on these findings we propose that the lectin sensitizes B cells for TLR stimulation as described for B cell receptor ligation and that B cell mitogenicity of PWM preparations results from synergistic activity of the poke weed lectin and microbial TLR ligands present in the PWM preparations.
Published January 4, 2012
Gesehen am 21.06.2018